Impact Analysis of Reinforced Concrete Columns with Side Openings Subjected to Eccentric Axial Loads (Journal of Engineering, 2015)
In this research the behavior of reinforced concrete columns with large side openings under impact loads was studied. The overall cross sectional dimensions of the column specimens used in this research were (500*1400) mm with total height of (14000) mm. The dimensions of side openings were (600*2000) mm. The column was reinforced with (20) mm diameter in longitudinal direction, while (12) mm ties were used in the transverse direction. The effect of eccentric impact loads on the horizontal and vertical displacement for this column was studied.                                                                                                                             Nonlinear finite element analysis has been carried out using ready computer finite element package (ANSYS) to simulate the behavior of the reinforced concrete column with large side openings. Two load cases were considered in this investigation (C1, C2) with three different load values for each case. In the first case (C1) the loads was applied to one side of the column and in the second case (C2) the loads was applied to both sides. An Equilateral triangular load-time function was used for simulation the impact load results from gantry cranes supported by the column with total time duration (0.1 sec).In order to verify the analysis method, as no experimental data exist for comparing the obtained results, another analysis is made for tested conventional column under impact load at mid-height and good agreement has been obtained.For the above mentioned column, the maximum displacements were (33.3, 22.2) mm in the horizontal and longitudinal direction respectively, location of the maximum horizontal displacement was at the crown of the column. By comparing the results of the first loading case with the second one it is shown that in the horizontal direction, maximum displacement increases by (139%), (208%), and (147%) respectively, also the maximum vertical displacement increases by (150%), (172%), and (172%) respectively.